Necessary conditions for the convergence of cardinal splines as their degree tends to infinity - 373654 Goodman, T. N. T.; Universiti Sains Malaysia. Pusat Pengajian Sains Matematik (Pulau Pinang : Pusat Pengajian Sains Matematik, Universiti Sains Malaysia, 1978)
41